Triptolide increases resistance to bile duct ligation-induced liver injury and fibrosis in mice by inhibiting RELB - Yuan, Zihang; Wang, Jie; Zhang, Haoran; Miao, Yingying; Tang, Qianhui; Yuan, Ziqiao; Nong, Cheng; Duan, Zhicheng; Zhang, Luyong; Jiang, Zhenzhou; Yu, Qinwei (Frontiers in Nutrition, 2022)
Cholestasis is a common, chronic liver disease that may cause fibrosis and cirrhosis. Tripterygium wilfordii Hook.f (TWHF) is a species in the Euonymus family that is commonly used as a source of medicine and food in Eastern and Southern China. Triptolide (TP) is an epoxy diterpene lactone of TWHF, as well as the main active ingredient in TWHF. Here, we used a mouse model of common bile duct ligation (BDL) cholestasis, along with cultured human intrahepatic biliary epithelial cells, to explore whether TP can relieve cholestasis. Compared with the control treatment, TP at a dose of 70 or 140 μg/kg reduced the serum levels of the liver enzymes alanine transaminase, aspartate aminotransferase, and alkaline phosphatase in mice; hematoxylin and eosin staining also showed that TP reduced necrosis in tissues. Both in vitro and in vivo analyses revealed that TP inhibited cholangiocyte proliferation by reducing the expression of RelB. Immunohistochemical staining of CK19 and Ki67, as well as measurement of Ck19 mRNA levels in hepatic tissue, revealed that TP inhibited the BDL-induced ductular reaction. Masson 3 and Sirius Red staining for hepatic hydroxyproline showed that TP alleviated BDL-induced hepatic fibrosis. Additionally, TP substantially inhibited BDL-induced hepatic inflammation. In summary, TP inhibited the BDL-induced ductular reaction by reducing the expression of RelB in cholangiocytes, thereby alleviating liver injury, fibrosis, and inflammation.